2017
DOI: 10.7243/2055-091x-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical staining of lipid droplets with adipophilin in paraffin-embedded glioma tissue identifies an association between lipid droplets and tumour grade

Abstract: Background: Cytoplasmic lipid droplets are important in cancer metabolism and a clear relationship has been established between their accumulation and increased tumour grade in glioma. The development of the novel immunohistochemical marker adipophilin has proven to be a useful method of detecting lipid droplets in paraffin embedded tissue from many diseases. Our aim was to assess the distribution of adipophilin stained lipid droplets in paraffin embedded glioma tissue and to evaluate whether it is a useful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…This includes the most common and lethal form of cancer in the brain, glioblastoma ( Taïb et al, 2019 ). While undetectable in low-grade gliomas, lipid droplet formation correlates with progression to advanced-stage glioblastomas ( Geng et al, 2016 ; Kohe et al, 2017 ). This is caused by an up-regulation of DGAT1 by glioblastomas, leading to increased production of neutral lipids ( Cheng et al, 2020 ).…”
Section: Lipid Droplets In the Diseased Brainmentioning
confidence: 99%
“…This includes the most common and lethal form of cancer in the brain, glioblastoma ( Taïb et al, 2019 ). While undetectable in low-grade gliomas, lipid droplet formation correlates with progression to advanced-stage glioblastomas ( Geng et al, 2016 ; Kohe et al, 2017 ). This is caused by an up-regulation of DGAT1 by glioblastomas, leading to increased production of neutral lipids ( Cheng et al, 2020 ).…”
Section: Lipid Droplets In the Diseased Brainmentioning
confidence: 99%
“…The role of lipids droplets in brain tumours is not well understood; however, there is evidence suggesting the number of lipid droplets increases in response to cellular stress and are associated with growth arrest 38 and necrosis 34 . Furthermore, the number of cells positively stained for adipophilin, a lipid droplet associated protein, was shown to significantly increase with tumour grade 39 .…”
Section: Discussionmentioning
confidence: 97%
“…The accumulation of LDs is a common finding in the tissues after ischemic injury, as seen in atherosclerosis or organ infarct [ 7 ]. Ischemia followed by activation of hypoxic signaling is a typical finding of malignant tumors, and is strongly associated with aggressive behavior [ 9 , 10 ]. Recent studies demonstrated that the fractional contribution of glutamine to fatty acid synthesis increased during hypoxia [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of LDs best be facilitated by the immunohistochemical expression of adipophilin, a vehicle of small LDs in non-adipogenic cells [ 8 ]. The role of adipophilin in cancer was recently investigated, and it was found to be not only a diagnostic marker, but also an independent poor prognostic marker for certain cancers, including clear cell renal cell carcinoma and brain glioma [ 9 , 10 ]. However, studies about the prognostic value of adipophilin in lung cancer were limited, and the association between the adipophilin and hypoxic ischemic pathways remains unclear.…”
mentioning
confidence: 99%